Use of Friction Pendulum System for Seismic Isolation of Museum Artifacts: Mathematical Modeling and Parametric Study - Celik, Abdullah; Azeloglu, Cumhur Oktay (GAZI UNIV, 2024)
Earthquakes seriously threaten precious artifacts in museums worldwide. Many historical pieces of inestimable importance that are considered the common heritage of humanity have been damaged by earthquakes. Robust measures must be put in place to protect museum artifacts from the perils associated with seismic risks. Seismic isolation devices like spherically shaped bearings are one of the best options to prevent seismic damage of museum artifacts thanks to achieving a long period under low weights. Therefore, the objective of this research is to assess the effectiveness of friction pendulum-type isolators, one of the spherically shaped bearings, in seismic isolation of museum artifacts and to identify the appropriate design parameters. In this study, a non-isolated single-degree-of-freedom model and a 2-degree-of-freedom model isolated with a friction pendulum bearing inside a building were established for a museum artifact. A parametric study was conducted using the RMS and the peak accelerations and displacements of the isolated mass at different values of friction coefficient and effective radius of curvature, as well as the maximum displacement of the friction pendulum system. Afterward, the non-isolated and isolated mass responses were compared in the time domain based on selected fmax= 0.06 and fmin= 0.03, Reff = 3 m parameters obtained from the parametric study. The simulation results demonstrate a substantial reduction in the acceleration values of the museum artifact, while simultaneously maintaining the relative displacement between the floor and the museum artifact within acceptable limits.
Keywords: Seismic isolation; friction pendulum system; museum artifact; BASE-ISOLATION; PROTECTION; EQUIPMENT; DESIGN; Engineering